Analisa Penegakan Hukum Pidana Perikanan di Indonesia - Robiyanoor, Robiyanoor (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Enforcement of fisheries criminal law in Indonesia is an important effort to protect fisheries resources from the threat of Illegal, Unreported, and Unregulated (IUU) Fishing. This study aims to analyze the challenges and solutions in enforcing fisheries criminal law through a literature review. The research method used is literature study by analyzing secondary data from various sources, including scientific journals, books and statutory regulatory documents. The research results show that the main challenges in enforcing fisheries criminal law in Indonesia include incompatibility between national policies and local implementation, limited human resources and technology, and corruption problems. To overcome this problem, it is necessary to increase coordination between agencies, increase human resource capacity, and use more sophisticated technology. This study concludes that integrated and sustainable efforts are needed to increase the effectiveness of law enforcement in the fisheries sector in Indonesia